Quality assessment of trauma care in a teaching hospital in North Western Nigeria - Gwaram, Usman; Sheshe, Abdurrahman; Adamu, Kabir; Abubakar, Mohammed; El‑Yakub, Amina; Mamuda, Abdurrahman; Inuwa, Ismail (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: The quality of care assessment is important to improve performance. The aim of this study is to assess the quality of trauma care in Aminu Kano Teaching Hospital, through the mortality methodology and analyze the failures of care.Materials and Methods: All patients above 18 years that died from trauma from 1st January 2012 to 31st December 2012 in the accident and emergency unit of AKTH were studied. Bio-demographic data, cause of injury, mode of presentation, time interval between injury and death and probable causes of death were recorded. A panel of surgeons reviewed these and failures of care were analyzed and categorised.Results: Out of 63 mortalities in the unit, only 58 (92%) had complete data for inclusion in the study. Forty-seven (81%) were from road traffic accident, six (10%) were gunshot wounds, four (7%) were fall and one from assault. Their age ranged from 18 to 76 with a mean of 31.9 years. There were 49 males and 9 females. Thirty (52%) were head injured, three mortalities (5%) had extremity injury, one each had abdominal and spinal injuries while 23 (40%) were multiply injured. Forty-nine (85%) patients had clearly identified failures of care. Seventeen of the head injuries were awaiting transfer to Intensive Care Unit (ICU) before death and 13 had airway problems at presentation. Of the non-Central Nervous System mortalities, six were fluid resuscitation and haemorrhagic shock, two had missed injuries, eight were from sepsis two of which were poorly controlled diabetics and two patients died from tetanus.Conclusion: There is high rate of failures of care directly contributing to the trauma mortality, mostly in head injuries. We recommend increased capacity of the ICU and involvement of anaesthetist in major trauma resuscitation for airway management to reduce the mortalities.
Keywords: Management failures; quality assessment; trauma care